The Realization of People's Sovereignty Through Recall of People to Elected Legislative Members - Lukman Nulhakim; Siti Rodhiyah Dwi Istinah (Jurnal Daulat Hukum, 2021)
The purpose of this study is to analyze the recalling system of legislative members in Indonesia that does not reflect the value of Pancasila justice; as well as obstacles and solutions to the recalling of legislative members in Indonesia that fulfill a sense of justice and Pancasila values. The research method used is an empirical juridical approach. Research conclusions is the recalling system for legislative members in Indonesia has not reflected the value of Pancasila justice, especially the four principles of Pancasila, namely democracy led by wisdom/deliberation, and eliminating the election system based on Open Proportionality, where constituents do not choose parties but elect candidates. Obstacles in recalling legislative members in Indonesia restrain legislative members from voicing their opinions and their efforts to fulfill the demands of their constituents and their nation, and make legislators no longer become representatives of the people but merely party officials. Recalling members of the legislature should be returned to the sovereignty of the people through the General Election Commission which determines and determines the elected legislative member, whether an elected legislative member can be recalled by his party or not, and as a form of people's sovereignty, regulations should be made regarding terms, conditions and procedures of people from the electoral area of elected legislative members to be able to recall the legislative members who are representing them to the General Election Commission, and if there is a dispute between the people recalling the recalled members or their political parties, the dispute can be carried out through the Constitutional Court or Supreme Court.